Corruption of blood - Tanenbaum, Robert (New York, N.Y., U.S.A. : Signet, 1996)
A Manhattan Assistant District Attorney heads a Congressional investigation into the assassination of John F. Kennedy.
Originally published: New York : Dutton, c1995.
Keywords: Kennedy, John F -- 1917-1963 -- Assassination -- Fiction; Karp, Butch (Fictitious character) -- Fiction; Public prosecutors -- Fiction